Iodide-Assisted Pd Catalysis as an Attractive Alternative to Rh Catalysis for the Industrially Relevant Isoselective Hydroformylation of Simple Aliphatic Alkenes - Zhang, Yang; Sigrist, Michel; Martínez, Sebastián; Bojanowski, Jan; Antheaume, Cyril; Granda, Jarosław M.; Dydio, Paweł (Synlett, 2023)
The hydroformylation of simple aliphatic alkenes, such as propylene, is one of the largest homogenous catalyzed processes in the chemical industry, producing over 10 million metric tons of different aldehydes each year. Typically, such processes are catalyzed by Co or Rh catalysts, yielding mostly linear aldehydes, such as n-butanal. However, the increasing demand for branched aldehydes, such as isobutanal, triggered further investigation to develop efficient isoselective protocols, which remain scarce. In this Synpacts article, we discuss our recent work on iodide-assisted Pd catalysis as an attractive alternative strategy for the development of isoselective methods. This article is presented considering the state of the art for Rh-catalyzed processes. Additionally, we discuss the limitations and challenges that need to be addressed in order to successfully transfer the technology to industry.1 Introduction2 State of the Art for the Isoselective Rh-Catalyzed Hydroformylation of Unbiased Aliphatic Alkenes2.1 Decomposition-Driven Isoselectivity2.2 Substrate-Dependent Isoselectivity2.3 Equiselective Catalysis2.4 Isoselective Rh Catalysts Bearing Small-Bite-Angle Ligands2.5 Isoselective Rh Catalyst Bearing a Tridentate Ligand2.6 Isoselective Catalysis Driven by Rh Encapsulation2.7 Isoselective Catalysis Driven by Specific Noncovalent Substrate–Ligand Interactions3 Pd-Catalyzed Isoselective Hydroformylation of Unbiased Aliphatic Alkenes3.1 Selectivity Patterns in Pd-Catalyzed Hydroformylation of Alkenes3.2 Unusual Iodide-Assisted Binuclear Pd(I)–Pd(I) Mechanism3.3 Development of Pd-Catalyzed Isoselective Hydroformylation of Unbiased Aliphatic Alkenes4 Conclusions and Outlook
Keywords: hydroformylation; selectivity; palladium; transition metal; aldehydes; hydrocarbons; isobutanal